2018
DOI: 10.1016/j.ijwd.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

A review of diagnosis and treatment of acne in adult female patients

Abstract: This review focuses on the treatment options for adult female patients with acne. Acne in adult female patients may start during adolescence and persist or have an onset in adulthood. Acne has various psychosocial effects that impact patients’ quality of life. Treatment of acne in adult women specifically has its challenges due to the considerations of patient preferences, pregnancy, and lactation. Treatments vary widely and treatment should be tailored specifically for each individual woman. We review convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
166
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(214 citation statements)
references
References 256 publications
(332 reference statements)
1
166
0
12
Order By: Relevance
“…ATRA is an established pleiotropic modulator of innate and adaptive immunity . In addition, topical application of ATRA is approved by the FDA for acne treatment . and represents a feasible choice for a combination strategy.…”
Section: Non‐ablative Fractional Laser Adjuvantmentioning
confidence: 99%
See 1 more Smart Citation
“…ATRA is an established pleiotropic modulator of innate and adaptive immunity . In addition, topical application of ATRA is approved by the FDA for acne treatment . and represents a feasible choice for a combination strategy.…”
Section: Non‐ablative Fractional Laser Adjuvantmentioning
confidence: 99%
“…56 In addition, topical application of ATRA is approved by the FDA for acne treatment. 57 and represents a feasible choice for a combination strategy. In this study, ATRA stimulated upregulation of cytosolic nucleic acid sensors and their downstream factors, leading to enhancement of type I interferon expression caused by release of DAMPs upon the NAFL treatment.…”
Section: Laser Adjuvantmentioning
confidence: 99%
“…Cortexolone 17αpropionate competitively inhibits endogenous androgen binding at the human androgen receptor level without inhibiting the skin 5α-reductase. Cortexolone 17α-propionate 1% cream was also clinically more effective than tretinoin 0.05% cream but this difference was not statistically significant [98]. Stearoyl-CoA desaturase-1 (SCD-1) catalyzes the formation of delta9-monounsaturated fatty acids from saturated precursors.…”
Section: Topical Anti-androgensmentioning
confidence: 99%
“…Oral isotretinoin is FDA-approved for the treatment of severe recalcitrant AV but can also be used to treat patients with moderate acne that is either treatment-resistant or relapses quickly after discontinuation of oral antibiotic therapy. Several studies have shown that isotretinoin effectively decreases sebum production, the number of acne lesions, and acne scarring [98]. The treatment for the average patient is carried out during two to ten months [248].…”
Section: Isotretinoinmentioning
confidence: 99%
See 1 more Smart Citation